The Parenting and Substitute Parenting of Young Children - Helen Penn (Substitute Parents, 2009)
Sociobiologists and primatologists, such as Sarah Hrdy (Prologue) have documented the evolutionary roots of primate behaviour. They have emphasized the variability of maternal and paternal behaviour across species. They also point to the ubiquitousness of alloparenting. Whether they live in gregarious communities, or whether they live more solitary lives, primate mothers are likely to have some direct help in rearing their young. In this chapter, I propose to examine some of the variations in parenting and alloparenting/substitute parenting which exist cross-culturally. I realize that the word ‘cross-cultural’ itself raises conceptual and methodological issues about the possibility of comparing very different